PS-081 Implementation of a pharmaceutical care programme for patients treated with investigational oral drugs in a clinical trials unit. (24th February 2014) - Riu, G; Gaba, L; Victoria, I; Molas, G; Do Pazo, F; Creus, N; Vidal, L
Abstract : Background: Oral agents provide an attractive approach to chemotherapy and their use is increasing. However, it is necessary to educate the patient to achieve adherence, avoid interactions and manage adverse effects correctly. When considering an investigational drug, the complexity increases: it is difficult to identify drugs because of their presentation (packaging and labelling) which leads to an increased number of medicines-related problems. Purpose: To implement a pharmaceutical care (PC) programme for oral investigational drugs in the Oncology Clinical Trials Unit of a tertiary hospital. Materials and methods: Prospective and descriptive intervention study conducted in cancer patients receiving oral investigational chemotherapy. The PC programme was structured in interviews. Demographic data, level of patient knowledge about the prescribed treatment and the usual medicines review to identify drug interactions were collected in the first visit. Subsequent follow-up interviews were aimed to assess adherence and conduct a patient satisfaction survey. Results: The process of implementing a PC programme was conducted properly. Fifty-one patients were included (median age 59 years (36–74); 28 males). 50.1% of patients admitted having doubts about the treatment. 49.0% did not know how to take the medicines in relation with food and 80.4% did not know what to do if they forgot or vomited a dose. The overall adherence rate was 98.7%. Six interactions were detected and 20 interventions were made (13 related to drug interaction information). The reasons for non-adherence were missed doses (2 cases) and voluntary decision (3 cases). 78.0% of patients had learned something new about their treatment after the interview and 92.0% were in favour of the programme. Conclusions: Patients are often incompletely informed about their investigational treatment. Due to the good results of adherence and patient satisfaction, patients should be educated individually to ensure effectiveness and safety. No conflict of interest.